Transcatheter closure of large atrial septal defects (ASDs) in symptomatic children with device/weight ratio ≥1.5. (15th September 2018) - Houeijeh, Ali; Hascoët, Sebastien; Bouvaist, Hélène; Hadeed, Khaled; Petit, Jérôme; Godart, François; Fraisse, Alain
Abstract: Background: Atrial septal defects (ASDs) can be symptomatic in small children in cases of co-morbidities. Transcatheter closure remains controversial for large defects in small children. Objective: To describe transcatheter closure of ASDs in children with device/weight ratio ≥1.5. Methods: We retrospectively studied between January 2000 and January 2016 all cases of percutaneous ASD closure with device/weight ratio ≥1.5 in 6 European centres. Results: Forty patients were included with female/male ratio of 1.2. Median age and weight were 30.9 months (4.1–102.0) and 11.0 kg respectively (3.8–19.0). Median device size/weight ratio was 1.7 (1.5–2.3). All patients were symptomatic, with pulmonary hypertension in 13 (33%). Procedures were performed under general anesthesia or light sedation (n = 4), with transthoracic (n = 25) or transesophageal echocardiography (n = 15) guidance. Balloon stretched diameter (n = 32) was larger than the echocardiographic diameter (19 versus 15 mm, R = 0.6; p < 0.001). Deficient rims other than the anterior-superior one were found in 33% of cases. Device implantation was successful in 39 patients (97.5%). Minor complications occurred in 10% of cases, whereas severe complications rate was 5%: Complete atrioventricular block in one patient that resolved after surgical extraction of the device and thrombosis in the inferior vena cava in one patient. During a median follow-up of 52 months, there was no residual shunt. No case of erosion or embolization was reported and pulmonary hypertension resolved in all patients. Conclusion: Percutaneous closure of large ASD in small and symptomatic children is feasible and allows clinical improvement with acceptable rate of complications in high risk population. Highlights: Closure of ASDs is often beneficial in small symptomatic children. Closure of large ASDs in children is often postponed to avoid complications. Closure of ASDs with device/weight >1.5 is feasible with high success rate. The complications rate is acceptable in such high risk population. Large ASDs closure in this population allows clinical improvement.